2017
DOI: 10.3892/ol.2017.7149
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of peritoneal dissemination in gastric cancer (Review)

Abstract: Abstract. Peritoneal dissemination is the most frequent metastatic pattern of gastric cancer, but the mechanisms underlying peritoneal dissemination are yet to be elucidated. Paget's 'seed and soil' hypothesis is recognized as the fundamental theory of metastasis. The 'seeding' theory proposes that the formation of peritoneal dissemination is a multistep process, including detachment from the primary tumour, transmigration and attachment to the distant peritoneum, invasion into subperitoneal tissue and prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 91 publications
(111 reference statements)
2
52
0
Order By: Relevance
“…It has been reported that E-cadherin is one of important factors for tumor invasion and distant metastasis in some solid cancers [8,[10][11][12]. Taken together, we previously reported the correlation between the microscopic distance from the tumor invasion front to the serosa (DIFS) and serosal exposure of gastric cancer cells, and speculated that DIFS might be associated with peritoneal recurrence [3].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…It has been reported that E-cadherin is one of important factors for tumor invasion and distant metastasis in some solid cancers [8,[10][11][12]. Taken together, we previously reported the correlation between the microscopic distance from the tumor invasion front to the serosa (DIFS) and serosal exposure of gastric cancer cells, and speculated that DIFS might be associated with peritoneal recurrence [3].…”
Section: Introductionmentioning
confidence: 55%
“…The exposure of cancer cells to the serosal surface (i.e., T4) is a common risk factor for and accounts for most cases of peritoneal recurrence [8,9]. However, peritoneal recurrence can develop in not only T4 cases but also cases without the exposure of cancer cells to the serosal surface (i.e., T3).…”
Section: Introductionmentioning
confidence: 99%
“…CAFs play a crucial role in the tumor's metastatic potential [134]. They stimulate an epigenetic change in microRNA (miR)-200, reducing its expression and thus promoting cancer invasion and peritoneal dissemination [135].…”
Section: Fibroblasts and Tumor Metastasismentioning
confidence: 99%
“…The relatively high mortality in GC is linked with its strong potential to form metastases, mainly via epithelial-mesenchymal transition (EMT) process when epithelial cells lose their polarity and adhesion features while gaining migratory and invasive properties to become mesenchymal stem-like cells [8].…”
Section: Introductionmentioning
confidence: 99%